2017
DOI: 10.15171/ijer.2017.03
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Drug Use and its Correlations Among Hookah Users in Khalil Abad, Northeast of Iran

Abstract: Background and aims: One of the most important problems of public health is illicit drug use. The aim of this study was to assess the status of illicit drug use and associated factors among hookah smokers in Khalil Abad city in 2015. Methods: The cross-sectional study was conducted in Khalil Abad city (northeast of Iran) in 2015. A sample of 161 hookah users was selected using 2-stage sampling. Structured questionnaires were distributed among the subjects and participants were included in the study after compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The results of the present study indicated that the prevalence of illicit drug use was higher among the male students compared to the females. The previous studies in Iran and other countries have also revealed that male students are more likely to use illicit drugs compared to females (15,25,26,33). The higher odds of illicit drug use by male students could be due to the higher availability of il-licit drugs to men, as well as their pleasure-seeking nature and more freedom, independence, and risk-taking behaviors.…”
Section: Discussionmentioning
confidence: 91%
“…The results of the present study indicated that the prevalence of illicit drug use was higher among the male students compared to the females. The previous studies in Iran and other countries have also revealed that male students are more likely to use illicit drugs compared to females (15,25,26,33). The higher odds of illicit drug use by male students could be due to the higher availability of il-licit drugs to men, as well as their pleasure-seeking nature and more freedom, independence, and risk-taking behaviors.…”
Section: Discussionmentioning
confidence: 91%